Parallel Compilers Are Coming Just in Time - Manuel, Tom; Curran, Lawrence (Electronics, 1988)
Parallel compilers for multiprocessor computing, while in the infancy stage, are delivering some remarkable performance improvements to old programs when they are run on parallel machines.